Penyelenggaraan Pendidikan Kristen Sebagai Pemenuhan Hak Asasi Manusia - Clartje Silvia E. Awulle (Sekolah Tinggi Teologi IKAT Jakarta, 2020)
This paper examines the organization of Christian education by the Theological College in the context of the fulfillment of human rights in the field of education. The writing of this paper uses qualitative discription methods and literature studies. In the context of human rights, the right to education is categorized as a positive right (positive right) because to realize these rights, it really requires an active role of the state so that the formulation of the right to education uses the term right to (right to) meaning that every citizen has the right to proper education as a basic human right that must be protected and fulfilled by the state with the aim that humans are protected their dignity, welfare and continuity of life. Having the opportunity to attend Christian education is a basic right of every Indonesian citizen who is a Christian who must be protected, guaranteed and fulfilled by the state. In the end all Christian citizens have the same opportunity to enjoy Christian higher education as a national education sub-system without discrimination. Abstrak Makalah ini mengkaji mengenai penyelenggaraan pendidikan kristen oleh Sekolah Tinggi Theologi dalam konteks pemenuhan hak asasi manusia (HAM) di bidang pendidikan. Penulisan makalah ini menggunakan metode qualitative discription dan studi literatur. Dalam konteks HAM, hak atas pendidikan dikategorikan sebagai hak positif (positive right) karena untuk merealisasikan hak-hak tersebut, sangat membutuhkan peran aktif negara sehingga rumusan hak atas pendidikan menggunakan istilah right to (berhak atas) artinya setiap warga negara berhak atas pendidikan yang layak sebagai hak dasar manusia yang harus dilindungi dan dipenuhi oleh negara dengan tujuan agar manusia terlindungi martabat, kesejahteraannya dan kelanjutan kehidupannya. Memperoleh kesempatan untuk mengikuti pendidikan kristen adalah hak dasar setiap warga negara Indonesia yang beragama kristen yang wajib dilindungi, dijamin dan dipenuhi oleh negara. Pada akhirnya semua warga negara Kristen memiliki kesempatan yang sama untuk menikmati pendidikan tinggi kristen sebagai sub sistem pendidikan nasional tanpa diskriminasi.